Intermittent hypobaric hypoxia and neuroendocrine reaction of the parvocellular neurons of the paraventricular hypothalamic nucleus - V. O. Shamenko; Ye. V. Kadzharian; A. V. Abramov (Patologìâ)
The neuroendocrine system occupies an important place in the systemic mechanisms of the body response to stress. The paraventricular nuclei of the hypothalamus (PVH) are one of the most important links of the brain`s neuroendocrine system which determine the reactivity of the hypothalamic-pituitary-adrenal axis (HPA) in response to the various stressors and thereby ensure the development of adaptive reactions by the formation of body resistance to the stress.